HNTs‐templated preparation of carbon nanorods by nanocasting method. (1st April 2017) - Liu, Zan; Cheng, Zhi‐Lin; Liu, Ying‐Ying
Abstract : Carbon nanorods (CNRs) have been attracting increasing interest because of their potential applications in high‐performance nanoscale materials and electronic devices. Among the many preparation methods, the nanocasting method via inorganic template materials exhibited a controllable and facile feature. This work was to present a novel preparation of CNRs through the nanocasting method using halloysite nanotubes (HNTs) as the template and polyvinyl alcohol (PVA) as the nanocasting carbon source. For the sake of PVA nanocasted in the hollow structure of HNTs, we adopted the repeated soakage method. The forming process and structure of CNRs were revealed by XRD, FT‐IR, SEM, TEM, SAED XPS, Raman and Brunner–Emmet–Teller (BET) characterisation techniques. The results showed that the as‐obtained CNRs with the rod‐like structure had a high specific surface area of ca. 284 m 2 /g and exhibited typical mesoporous features.